Environmentally Benign Synthesis of Tetra-Substituted Imidazoles through 4-Components Strategy Mediated by (S)-3-Methyl-1, 1-Diphenylbutane-1, 2-Diamine (Journal of Scientific Research, 2018)
(S)-3-Methyl-1, 1-diphenylbutane-1, 2-diamine has been found to be a mild and effective organocatalyst for one-pot 4-components synthesis of 1, 2, 4, 5-tetra-substituted imidazoles. The key benefits of this protocol is high yielding, cost effectiveness, easy purification and above all, environmentally benign.